Identifying the Drivers of the Exceptionally High Rates of Lethal and Racially Biased Violence by Police in the United States Requires Geographically Resolved Data and Analysis. Issue 1 (28th December 2015) - Ross, Cody T.
Abstract : This essay serves as a response to Hirschfield's (2015) article, "Lethal Policing: Making Sense of American Exceptionalism, " published in the December 2015 issue of this journal.